Barriers in the Implementation of Health Information Systems: A Scoping Review - Florin STAMATIAN; Cătălin Ovidiu BABA; Mara Paula TIMOFE (Transylvanian Review of Administrative Sciences, 2013)
Context. A well-developed health information system which is implemented according to present standards allows a healthcare quality increase. Our study aims at providing an overview of the barriers which were encountered in the process of implementing the health information systems by reviewing the literature connected to Europe and the United States of America. Methodology. We searched within five databases (Cochrane Library, Google Scholar, PubMed, ScienceDirect and Scopus) for the exact phrase ‘implementation health information system’ along with the name of each European country/USA state. Relevance was then tested by scanning titles and abstracts. The third and final step involved assessing all the articles in order to set their relevance and a data extraction tool was created, containing the name of the state/country that the article reports data on, the article citation and the challenges identified. Results. The barriers identified were classified in four major categories: technical, organizational, behavioral/human and financial. Seemingly, Europe (41 articles) and USA (20 articles) are facing the same issues in the implementation of a health information system. No major difference between EU and non-EU countries was found after our analysis with regards to the identified barriers. Discussion. Even if recommendations and solutions are continuously being developed in order to solve these barriers, the implementation of a new health information system must be very detailed in order to face all these problems. Additionally, further research is required in order to evaluate their impact on the successful implementation of a health information system.